Kajian Eksperimen Deffoormasi Tekanan Pada Struktur Sarang Lebah Dengan Variasi Ukuran Hexagonal Yang Diuji Secara Statis - Sudirman Lubis; Chandra A. Siregar; Irpansyah Siregar; Edi Sarman Hasibuan (Rekayasa Material, Manufaktur dan Energi, 2020)
Humans have always tried to create new materials that have a strong, rigid, lightweight, and inexpensive construction. The honeycomb structure is a man-made material that has a honeycomb geometry to minimize the amount of material used, to achieve a minimum weight so that a light mass is obtained for the construction. The honeycomb structure is commonly used in aerospace, transportation, F1 competitions, and many other industries. In general, the purpose of this study is to determine the level of deformation, strain stress that occurs in the honeycomb structure that is statically tested. Honeycomb is made using aluminum material with a thickness of 0.4 mm and then formed with a hexagonal size that varies with 2 mm, 4 mm, and 6 mm. This compressive test is carried out using a Universal Testing Machine with 2 positions namely horizontal and vertical. The specimen is pressed until it has a visible point on the graph. The results that have been found from this compressive test in the form of deformation values and the maximum force acting on the specimen. From the results of the comparison of hexagonal size variations, it can be concluded that the larger the hexagonal honeycomb size, the greater the deformation that occurs.